ANALYSIS OF EDUCATIONAL REFORM IN ECUADOR - Vásquez Flores, José Alberto (2014)
The present article seeks to analyze the educational reform in Ecuador from the new institutions of the country, which constitutes the government of Econ. Rafael Correa Delgado with the new educational model that began in January 2010, after the complete restructuring of the Ministry of Education, whose objective was to ensure the path to early education in Ecuador with quality and warmth, strengthening the education authority, deconcentration articulated a system that encourages an approach with citizens and access to free education at all levels: primary, se-condary and higher, with some necessary conditions.An introduction is drawn from educational reform succeeded in 1983, which originates four years later, the “Education Law” or Law 127, published in Official Record 484 of May 3, 1983.This analysis also helps to demonstrate concrete results or social and educational progress that has generated educational reform within the internal and external environment, based on the perspective of before and after, and how through, its application has been made to strengthen the processes to improve the quality, re-levance, equity and efficiency of education in Ecuador.